Magnetohydrodynamic effects in mixed convection copper-water nano fluid flow at lower stagnation point on a sliced sphere - Widodo, Basuki; Nugraha, Adhi Surya; Adzkiya, Dieky; Mohd Zuki, Salleh (Penerbit Akademia Baru, 2021)
The study of simulation and applications of mathematics in fluid dynamics continues to grow along with the development of computer science and technology. One of them is Magnetohydrodynamics (MHD) which is closely related to its implementation in engineering and industry. And given the importance of magnetic fluid flow has attracted researchers to study and explore its benefits and uses in the industrial field, especially in convective flow and heat transfer processes. This paper therefore considers mathematical modeling on mixed convection MHD viscous fluid flow on the lower stagnation point of a magnetic sliced sphere. The study began with transforming the governing equations which are in dimensional partial differential equations to non-dimensional ordinary differential equations by using the similarity variable. The resulting similarity equations are then solved by the Keller-Box scheme. The characteristics and effects of the Prandtl number, the sliced angle, the magnetic parameter, and the mixed convection parameter are analyzed and discussed. The results depicted that the uniform magnetic field produced by Lorentz force and slicing on the sphere act as determining factors for the trend of nano fluid movement and controlling the cooling rate of the sphere surface. In addition, the viscosity depends on the copper particle volume fraction.